Identifikasi Dan Penetapan Kadar Zat Warna Merah Dalam Dawet Secara KLT-Densitometri - Lanni Wijaya, Siti Surdijati, Andjar Sardjimah (Widya Mandala Surabaya Catholic University, 2001)
Red colorants are often used for coloring â€œdawetâ€ drinks sold along â€œXâ€ street in Surabaya. The red colorants are possibly those additive coloring agents not permitted for foods or those permitted but the contents exceeded that stated by the Indonesian Minister of Health Regulation No. 722/Menkes/Per/IX/1988/on Food Additives. In the qualitative and quantative tests using TLC-Densitometry with stationary phase : silica Gel GF254 , mobile phase : isopropanol : ammonia â€“ 4 : 1 and selected maximum wavelength 553 nm, it was found that be red colorant used was Rhodamin B, that was not permitted for foods and the contents found were 0.011 % to 0.016 %.